2021
DOI: 10.1007/s10815-021-02202-4
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of diandric and digynic triploidy depending on gestational age

Abstract: Purpose To establish the distribution of diandric and digynic triploidy depending on gestational age. Methods 107 triploid samples tested prospectively in a single genetic department during a four-year period were analyzed for parental origin of triploidy by Quantitative Fluorescent Polymerase Chain Reaction (QF-PCR) (n=95) with the use of matching parental samples or by MS-MLPA (n=12), when parental samples were unavailable. Tested pregnancies were divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A possible dyspermia may be the source of an extra set of paternal chromosomes. The prevalence of paternal (diandric) triploidy varies between 20% and 85% in various studies and the vast majority of them are lost in the first trimester of pregnancy [ 36 ]. Most triploidies may have paternal origin, and diandric triploidy can often be diagnosed as partial hydatidiform moles with abnormal placentas characterized by trophoblastic proliferation [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible dyspermia may be the source of an extra set of paternal chromosomes. The prevalence of paternal (diandric) triploidy varies between 20% and 85% in various studies and the vast majority of them are lost in the first trimester of pregnancy [ 36 ]. Most triploidies may have paternal origin, and diandric triploidy can often be diagnosed as partial hydatidiform moles with abnormal placentas characterized by trophoblastic proliferation [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also explore the correlation between gestational weeks and fetal chromosomal abnormalities. Previous research has suggested that the incidence of chromosomal abnormalities in fetuses is higher during early pregnancy than in the mid-pregnancy phase ( 30 ), and triploidy occurs more frequently in pregnancies of less than 11 weeks gestational age ( 41 ). However, we did observe no significant difference in the detection rates of fetuses with normal karyotypes in different gestational ages, and the proportion of mosaicisms in abnormal karyotypes decreased with increasing gestational age, while the proportion of sex chromosome monosomy and polyploidy in abnormal karyotypes increased with gestational week.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of diandric and digynic triploidy has been reported differently depending on gestational age. [22][23][24] Typically, digynic triploid conceptions do not display morphological features of molar pregnancy but on occasion can exhibit some focal dysmorphic features suggestive of a PHM. 7 25 A digynic triploid conceptus may manifest on ultrasound with a growth restricted fetus, with relative macrocephaly and a non-cystic placenta but these abnormalities can be subtle and may be missed in the first trimester.…”
Section: Original Researchmentioning
confidence: 99%